Gestational diabetes mellitus, prenatal maternal depression, and risk for postpartum depression: an Environmental influences on Child Health Outcomes (ECHO) Study - Lauren C. Shuffrey; Maristella Lucchini; Santiago Morales; Ayesha Sania; Christine Hockett; Emily Barrett; Kecia N. Carroll; Camille C. Cioffi; Dana Dabelea; Sean Deoni; Anne L. Dunlop; Arielle Deutsch; et al. (BMC, 2022)
Abstract Background Prior research has demonstrated bidirectional associations between gestational diabetes mellitus (GDM) and perinatal maternal depression. However, the association between GDM, prenatal depression, and postpartum depression (PPD) has not been examined in a prospective cohort longitudinally. Methods Participants in the current analysis included 5,822 women from the National Institutes of Health's Environmental influences on Child Health Outcomes (ECHO) Research Program: N = 4,606 with Neither GDM nor Prenatal Maternal Depression (Reference Category); N = 416 with GDM only; N = 689 with Prenatal Maternal Depression only; and N = 111 with Comorbid GDM and Prenatal Maternal Depression. The PROMIS-D scale was used to measure prenatal and postnatal maternal depressive symptoms. Primary analyses consisted of linear regression models to estimate the independent and joint effects of GDM and prenatal maternal depression on maternal postpartum depressive symptoms. Results A higher proportion of women with GDM were classified as having prenatal depression (N = 111; 21%) compared to the proportion of women without GDM who were classified as having prenatal depression (N = 689; 13%), however this finding was not significant after adjustment for covariates. Women with Comorbid GDM and Prenatal Maternal Depression had significantly increased postpartum depressive symptoms measured by PROMIS-D T-scores compared to women with Neither GDM nor Prenatal Maternal Depression (mean difference 7.02, 95% CI 5.00, 9.05). Comorbid GDM and Prenatal Maternal Depression was associated with an increased likelihood of PPD (OR 7.38, 95% CI 4.05, 12.94). However, women with GDM only did not have increased postpartum PROMIS-D T-scores or increased rates of PPD. Conclusions Our findings underscore the importance of universal depression screening during pregnancy and in the first postpartum year. Due to the joint association of GDM and prenatal maternal depression on risk of PPD, future studies should examine potential mechanisms underlying this relation.